A Qualitative Investigation of German Manufacturing Enterprises’ Efforts to Incorporate Sustainability Into Industrial Site Transformations - Ozen, Oskay; Ioshchikhes, Borys; Frank, Michael Georg; Weigold, Matthias (International Journal of Sustainable Energy Planning and Management, 2026)
As part of the European Green Deal, Germany is committed to greenhouse gas neutrality by 2045. To accommodate these goals, manufacturing enterprises are aiming to futureproof their sites through site transformations towards sustainability. Such efforts are affected by an inherent competition for usable space, as each successive transformation changes the overall site composition. Despite economic sustainability having the highest priority for enterprises, land is nonetheless being allocated to socio-environmental measures. To gauge current industrial efforts for sustainable transformation, a interview study with 19 experts was conducted. The experts represented the fields of site planning, facility management, and sustainability management. The study primarily focused on plans for next generational energy systems, including challenges faced during their planning and execution, supplemented by how land is used for further sustainability measures. The interviews were analyzed using Kuckartz’ qualitative content analysis. The results show proactive engagement by enterprises to meet climate goals ahead of regional policies. Within this scope, the goal of ensuring economic competitiveness is pursued through a variety of different means, such as security of energy supply, self-sufficiency, adaptability to new technologies and regulations, and staff retention. Organizational challenges were found to outweigh financial ones.